CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE FINANCIAL PERFORMANCE: PERAN MEDIASI STAKEHOLDERS INFLUENCE CAPACITY - Wisnu Dian Prawita (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
The purpose of this study is to find empirical evidence of the role of mediating stakeholder influence capacity (SIC) on the effect of corporate social responsibility (CSR) on corporate financial performance. This type of research is quantitative research with explanatory research approach to analyze the influence of variables examined in the research hypothesis. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2016 period. This research uses purposive sampling technique and uses statistical analysis of Structural Equation Model with Partial Least Square (SEM-PLS) approach with the help of WarpPLS 5.0 software. The results showed that CSR and SIC had a positive effect on corporate financial performance. This shows that the efforts of managers in carrying out CSR programs have an impact on increasing corporate financial performance, and increasing SIC has a good effect on improving corporate financial performance. In addition, CSR has a positive effect on SIC. This shows that the efforts of managers in improving CSR programs provide an attraction for stakeholders to increase their support for the company. The results of the study indicate that SIC can mediate the effect of CSR on corporate financial performance. This shows that the increase in SIC helps CSR in improving corporate financial performance